Jezikoslovno izrazje 19. stoletja - Pacek, Mojca (Slavistična revija, 2003)
The article attempts to illustrate the development of linguistics terminology in the 19th c. on the basis of Slovene grammars from this period. It presents the content (conceptual-theoretical) side of the grammars as well as the analysis of the linguistic terms on the expression, generative-transformational planes, and from the standpoint of borrowing, which proves the thesis about continuity in the development of linguistic terminology.
Keywords: 19.st.; linguistics; lingvistika; Slovene; slovenščina; terminologija; terminology